Study on microbial profile and antibiotic resistance patterns in culture proven neonatal sepsis: a three-year retrospective analysis from Rajarajeswari Medical College and Hospital, Bangalore, India - Sangireddy, Mounika; Ramachandra, Kartik; Venkataramaiah , Venkatesh Murthy Dammaningala (International Journal of Contemporary Pediatrics, 2026)
Background: Neonatal sepsis remains a significant cause of morbidity and mortality, particularly in developing countries, due to varying microbial patterns and rising antimicrobial resistance. Continuous surveillance of causative organisms and their antibiotic susceptibility is essential for effective management. The objective of the study was to analyze the microbial profile and antibiotic resistance patterns in culture-proven neonatal sepsis cases in a tertiary care hospital. Methods: A retrospective observational study was conducted over a period of three years (January 2023 to January 2026) in Rajarajeswari Medical College and Hospital, Bangalore. A total of 75 neonates with clinically suspected sepsis were included based on predefined inclusion and exclusion criteria. Blood culture reports, demographic details, and antibiotic susceptibility patterns were collected from hospital records. Microbial identification and antibiotic sensitivity testing were performed using standard microbiological methods in accordance with CLSI guidelines. Data were analyzed using descriptive and inferential statistics. Results: Among the 75 neonates, 61.33% were male and 85.33% presented with early-onset sepsis. The culture positivity rate was 36.00%. Klebsiella pneumoniae (44.44%) was the most common pathogen, followed by coagulase-negative Staphylococcus (18.52%) and Pseudomonas spp. (14.81%). Gram-negative organisms (59.26%) predominated over gram-positive organisms (40.74%). High sensitivity (100%) was observed for cefotaxime, ceftazidime, amikacin, meropenem, vancomycin, and linezolid. However, high resistance was noted for penicillin (70.83%), ampicillin (66.67%), and high-level gentamicin (75.00%). Multidrug resistance was observed in 66.67% of isolates. No statistically significant association was found between demographic factors and culture positivity (p>0.05). Conclusion: Neonatal sepsis in the present study was predominantly caused by gram-negative organisms with a high prevalence of multidrug resistance. While higher-generation antibiotics remain effective, increasing resistance to first-line drugs highlights the need for antibiotic stewardship, regular surveillance, and institution-specific treatment guidelines.